Loss And Gain In The Translation Process Of Bilingual Online News - Ida Ayu Made, Dian Wilasita; Putri Rahardian, Zabrina; Balqis Kusumah, Alifia; Agung Istri Aryani, I Gusti (Universitas KH. Mukhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2024)
This study examines the translation of bilingual online news headlines about Ed Sheeran's concert tour, focusing on the concepts of